Study on the effect of nitrogen content and cooling rate on the ferrite number of austenitic stainless steels - Vicente, André de Albuquerque; D'silva, Peter Aloysius; Sadanandan, Sibi; Santos, Tiago Felipe de Abreu; Tenório, Jorge Alberto Soares (International Journal of Advanced Engineering Research and Science, 2020)
In order to better understanding the effect of nitrogen content in shielding gases and different cooling rates on the volume fraction of δ ferrite in welded deposits through GTAW, the microstructures of four welded joints of austenitic stainless steel, were studied. The deposits were produced using the same welding electrode ER 316L2.4 mm and welding parameters, but different shielding gases from pure argon to mixture with N2, and different cooling rates. One pair of the welding deposits was produced with 100% Ar and the other one with 98% Ar+2% N2. The weld pads produced with the same shielding gas were submitted to different cooling rates, being cooled in air and water. The chemical compositions and the variation of the volume fractions of δ ferrite in the deposits were measured. It was observed pickup of nitrogen and, consequently, decreasing of the volume fraction of δ ferrite in the all weld metals produced with 98% Ar+2% N2as the shielding gas. The weld pads cooled in water presented less δ ferrite when compared to those produced using the same shielding gas but cooled in air. The results confirm that nitrogen is a strong austenite stabilizer and that higher cooling rates reduce the δ ferrite volume fraction in austenitic stainless steels. Complementary techniques of microstructural analysis were used, such as optical emission spectrometry, optical microscopy and quantitative image analysis.